Metallothionein, Copper and Alpha-Synuclein in Alpha-Synucleinopathies - Okita, Yuho; Rcom-H'cheo-Gauthier, Alexandre N.; Goulding, Michael; Chung, Roger S.; Faller, Peter; Pountney, Dean L. (Frontiers in Neuroscience, 2017)
Metallothioneins (MTs) are proteins that function by metal exchange to regulate the bioavailability of metals, such as zinc and copper. Copper functions in the brain to regulate mitochondria, neurotransmitter production and cell signalling. Inappropriate copper binding can result in loss of protein function and Cu(I)/(II) redox cycling can generate reactive oxygen species. Copper accumulates in the brain with ageing and has been shown to bind alpha-synuclein and initiate its aggregation, the primary aetiological factor in Parkinson’s disease (PD) and other alpha-synucleinopathies. In PD, total tissue copper is decreased, including neuromelanin-bound copper and there is a reduction in copper transporter CTR-1. Conversely cerebrospinal fluid (CSF) copper is increased. MT-1/2 expression is increased in activated astrocytes in alpha-synucleinopathies, yet expression of the neuronal MT-3 isoform may be reduced. MTs have been implicated in inflammatory states to perform one-way exchange of copper, releasing free zinc and recent studies have found copper bound to alpha-synuclein is transferred to the MT-3 isoform in vitro and MT-3 is found bound to pathological alpha-synuclein aggregates in the alpha-synucleinopathy, multiple systems atrophy. Moreover, both MT and alpha-synuclein can be released and taken up by neural cells via specific receptors and so may interact both intra- and extra-cellularly. Here, we critically review the role of MTs in copper dyshomeostasis and alpha-synuclein aggregation, and their potential as biomarkers and therapeutic targets.